2017
DOI: 10.1371/journal.pone.0173340
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising surveillance for alien organisms transported as stowaways on ships travelling to South Africa

Abstract: The global shipping network facilitates the transportation and introduction of marine and terrestrial organisms to regions where they are not native, and some of these organisms become invasive. South Africa was used as a case study to evaluate the potential for shipping to contribute to the introduction and establishment of marine and terrestrial alien species (i.e. establishment debt) and to assess how this varies across shipping routes and seasons. As a proxy for the number of species introduced (i.e. ‘colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
(111 reference statements)
0
14
0
Order By: Relevance
“…Such models have also been used to predict future potential invaders, e.g. to assist in the development of a watch list of species (Faulkner et al 2014), and to inform surveillance efforts (Faulkner et al 2017). Importantly, however, the broad-scale environmental variables typically used as input to species distribution models permit only broad-scale predictions.…”
Section: Species Distribution Modelsmentioning
confidence: 99%
“…Such models have also been used to predict future potential invaders, e.g. to assist in the development of a watch list of species (Faulkner et al 2014), and to inform surveillance efforts (Faulkner et al 2017). Importantly, however, the broad-scale environmental variables typically used as input to species distribution models permit only broad-scale predictions.…”
Section: Species Distribution Modelsmentioning
confidence: 99%
“…It is likely that the long history of shipping there is linked to the high numbers of alien species observed in this ecoregion, at least for historical introductions. Interestingly, Durban harbour, in the Natal ecoregion, has received the highest number of international vessels in recent times (Faulkner et al 2017), demonstrating that vector strength alone does not explain the observed numbers of alien species. In fact, relative similarity of climate between donor and recipient regions may moderate invasion success of arriving species (Ashton 2006).…”
Section: Geographic Patterns Around a Variable Coastmentioning
confidence: 97%
“…26). Compared with many other countries on the continent, South Africa has considerable trade relations with the rest of the continent, and the world through several international airports and three large shipping ports (Faulkner et al 2017a). This affords it ample opportunity to have become an important donor.…”
Section: Non-south African Originsmentioning
confidence: 99%
“…South Africa is recognised as having had a long history as a major commercial hub for southern Africa, and in some cases for the continent (Faulkner et al 2017a). There are documented historical examples of how South Africa has acted as a bridgehead for invasions elsewhere on the continent (Lombaert et al 2010).…”
Section: South Africa As a Bridgehead For Invasionsmentioning
confidence: 99%